2006
DOI: 10.1007/s11194-006-9030-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Application of the Self-Regulation Model of the Relapse Process for Mainstream and Special Needs Sexual Offenders

Abstract: The self-regulation model of the relapse process (Ward & Hudson, 2000) has been developed and empirically validated on general sexual offender populations (Bickley & Beech, 2002), but not on specific sexual offender populations. This paper aims to investigate whether special needs offenders, as compared to mainstream sexual offenders, can be categorized into the offense pathways described in the model. In addition, this paper aims to evaluate the application of the self-regulation model in highlighting the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Importantly, these pathways may differ as a result of offender classification, and our results suggest that these offense pathways also apply within an Asian context. Consistent with Bickley and Beech’s (2002) and Keeling et al’s (2006) findings, the majority of the youth who sexually offended followed the Approach pathways. Closer examination of the offender classifications revealed that youth who committed penetrative offenses tended to follow the Approach pathways, whereas those who molested children tended to follow the Avoidant-Passive and the Approach-Automatic pathways; these findings were somewhat consistent with the literature about the offense pathways for adult rapists and child molesters ( Kingston et al, 2012 ; Yates & Kingston, 2006 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Importantly, these pathways may differ as a result of offender classification, and our results suggest that these offense pathways also apply within an Asian context. Consistent with Bickley and Beech’s (2002) and Keeling et al’s (2006) findings, the majority of the youth who sexually offended followed the Approach pathways. Closer examination of the offender classifications revealed that youth who committed penetrative offenses tended to follow the Approach pathways, whereas those who molested children tended to follow the Avoidant-Passive and the Approach-Automatic pathways; these findings were somewhat consistent with the literature about the offense pathways for adult rapists and child molesters ( Kingston et al, 2012 ; Yates & Kingston, 2006 ).…”
Section: Discussionsupporting
confidence: 74%
“…The scores for the dimension items were summed to obtain a Total Score for the Avoidant/Approach dimension (total score = 0-40) and Passive/Active dimension (total score = 0-50). Several studies have utilized this checklist (e.g., Bickley & Beech, 2002 ; Ford et al, 2009 ; Keeling et al, 2006 ; Langdon et al, 2007 ) and the interrater reliability was found to be moderate to excellent (kappa = .60-.83; see Cicchetti, 1994 , for a classification of kappa).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the smallest group was in the avoidant‐passive pathway. In examining the self‐regulation theory with sexual offenders with special needs (defined as including some individuals with intellectual disbaility but also higher functioning individuals with other deficits) compared with mainstream sexual offenders, Keeling et al. (2006) found no significant differences between representations in pathways between these two groups.…”
Section: Theories Of Sexual Offendingmentioning
confidence: 95%
“…Cognitive-behavioral therapies (CBT) are widely considered the mainstream treatment modality applied to rehabilitate general populations of sex offenders (Keeling, Rose, & Beech, 2008; Wilson, Bouffard, & Mackenzie, 2005; Witt, Greenfield, & Hiscox, 2008). Concerns have arisen, however, surrounding the applicability of traditional CBT modalities to populations of sex offenders, with intellectual and developmental disabilities (IDD; Keeling, Rose, & Beech, 2006a). Guided by the principle that programs must remain responsive to the unique psychosocial needs and risk of relapse presented by the individual, sex offender treatments have emerged that cater to the cognitive, emotional, and behavioral challenges presented by sex offenders with IDD (Allam, Middleton, & Browne, 1997; Aust, 2010; Beech & Ward, 2004; Blacker, Beech, Wilcox, & Boer, 2011; Keeling, Rose, & Beech, 2006b; Taylor, Lindsay, & Willner, 2008).…”
Section: Introductionmentioning
confidence: 99%